Driving decisions of older adults receiving meal delivery: The influence of individual characteristics, the built environment, and neighborhood familiarity. (June 2016) - Hess, Daniel Baldwin; Norton, J. Travis; Park, JiYoung; Street, Debra A.
Highlights: We model driving behavior for older adults receiving home meal delivery. We examine social, weather, and built environment factors affecting driving. Driving is critical to overall mobility in the study population. Those with long housing tenure are more likely to drive. Age is associated with increases, rather than decreases, in the choice to drive. Abstract: Access and mobility are key ingredients to independence and life satisfaction for older adults. This research addresses a series of gaps in scholarly literature on driving behavior among community-dwelling older adults, particularly those who rely on in-home supportive services to age in place. We explore the influence of a series of factors, including individual attributes, family and household structure, general mobility, and weather preparedness on driving behavior. Using survey data for Meals on Wheels clients in the Town of Tonawanda, New York, a stable first-ring suburb with much aging in place, we construct binary logit models to explore the factors explaining the decision to drive or not. Our findings suggest that age is positively associated, but at a diminishing rate, with driving when health and functional limitations are controlled for; women have lower propensities than men for driving; those who drive have higher overall mobility; driving is negatively associated with mixed land uses near home; housing tenure (duration in years) is positively associated with driving. Weather-related variables are not statistically significant, but this does not diminish the potentially significant impacts of extreme weather events on mobility among older adults.